The impact of the COVID-19 epidemic on hospital admissions for alcohol-related liver disease and pancreatitis in Japan - Hisashi Itoshima (Nature Portfolio, 2021)
Abstract During the coronavirus disease 2019 (COVID-19) pandemic, there have been health concerns related to alcohol use and misuse. We aimed to examine the population-level change in cases of alcohol-related liver disease and pancreatitis that required admission during the COVID-19 epidemic by interrupted time series (ITS) analysis using claims data. We defined the period from April 2020, when the Japanese government declared a state of emergency, as the beginning of the COVID-19 epidemic. This ITS analysis included 3,026,389 overall admissions and 10,242 admissions for alcohol-related liver disease or pancreatitis from 257 hospitals between July 2018 and June 2020. The rate of admissions per 1000 admissions during the COVID-19 epidemic period (April 2020–June 2020) was 1.2 times (rate ratio: 1.22, 95% confidence interval: 1.12–1.33) compared to the pre-epidemic period. Analyses stratified by sex revealed that the increases in admission rates of alcohol-related liver disease or pancreatitis for females were higher than for males during the COVID-19 epidemic period. The COVID-19 epidemic in Japan might associates an increase in hospital admissions for alcohol-related liver disease and pancreatitis. Our study could support the concern of alcohol consumption and health problems during the COVID-19 pandemic.